2018
DOI: 10.1038/s41598-018-32018-9
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid Adaptation to the Timbre of Natural Sounds

Abstract: Timbre, the unique quality of a sound that points to its source, allows us to quickly identify a loved one’s voice in a crowd and distinguish a buzzy, bright trumpet from a warm cello. Despite its importance for perceiving the richness of auditory objects, timbre is a relatively poorly understood feature of sounds. Here we demonstrate for the first time that listeners adapt to the timbre of a wide variety of natural sounds. For each of several sound classes, participants were repeatedly exposed to two sounds (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
4
8
0
Order By: Relevance
“…What is interesting is that serial dependencies are not specific to the visual domain. Indeed, similar short-term dependencies have been reported within the auditory domain when participants were instructed to judge the direction of an auditory frequency sweep (Alais et al, 2015), the loudness (Holland & Lockhead, 1968;Jesteadt et al 1977), or the timbre (Piazza et al, 2018) of a sound. Serial dependencies have also been observed within the tactile domain when rats had to judge each vibrissae (or whiskers) vibration (Hachen et al, 2020).…”
Section: Introductionsupporting
confidence: 60%
“…What is interesting is that serial dependencies are not specific to the visual domain. Indeed, similar short-term dependencies have been reported within the auditory domain when participants were instructed to judge the direction of an auditory frequency sweep (Alais et al, 2015), the loudness (Holland & Lockhead, 1968;Jesteadt et al 1977), or the timbre (Piazza et al, 2018) of a sound. Serial dependencies have also been observed within the tactile domain when rats had to judge each vibrissae (or whiskers) vibration (Hachen et al, 2020).…”
Section: Introductionsupporting
confidence: 60%
“…In Experiment 1, we found timbre to play a larger role than F0 in vocal emotion adaptation. These findings are in line with Skuk et al (2015), who found very similar results for adaptation to vocal gender and with Piazza et al (2018), who suggested timbre as the critical parameter for auditory adaptation by showing rapid and robust aftereffects for a variety of natural sounds. However, the present results conflict with Hubbard and Assmann (2013), who argued that F0 is crucial for vocal emotion adaptation, after they failed to observe aftereffects in a F0-removed condition.…”
Section: The Role Of Timbre and F0 In Vocal Emotion Adaptationsupporting
confidence: 90%
“…Thus, vocal emotion adaptation may be affected by the auditory similarity between adaptors and targets, irrespective of speaker gender. For timbre-only adaptation, Piazza et al (2018) found aftereffects to be robust to moderate pitch changes, but to decrease with more substantial pitch differences, until they were only marginally measurable at 9 semitones difference. In our sample, F0 of male and female speakers differed by about 90 Hz, which corresponds to an average change of 5-6 semitones.…”
Section: Acoustical Proximitymentioning
confidence: 91%
See 2 more Smart Citations